(untitled) (World Economics and Finance Bulletin, 2023)
This article describes the necessity and importance of investing in human capital in the service sector, the specifics of investing in human capital in the service sector, and the algorithm for effective use of human capital in the service sector. The article also presents the results of investments in human capital, the factors affecting them, and the share of human capital in the countries of the world